Analisis Kelayakan Pasar dan Strategi Pemasaran pada Bisnis Buket From Me For You - Rahmawati, Anis Tri (Maliki Interdisciplinary Journal, 2025)
The From Me For You bouquet business is a creative business that offers personal and aesthetic products for various special moments such as birthdays, graduations and weddings. This research aims to analyze the market feasibility and marketing strategy of the business, with a focus on aspects of segmentation, market target and positioning. The analysis was carried out using a SWOT approach and a social media-based marketing strategy. The research results show that this business has large market potential in the upper middle class segment of society, supported by quality products, personalization and competitive prices. Promotional strategies through digital platforms such as Instagram, Facebook and WhatsApp are the main force in increasing visibility and competitiveness. However, challenges such as shipping costs and price competition must still be overcome with product innovation and strengthening customer service. This research is expected to provide strategic guidance for the development of a more sustainable bouquet business.